ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK SYARIAH DENGAN MENGGUNAKAN INCOME STATEMENT APPROACH DAN VALUE ADDED APPROACH - Dimas Pratama Putra (MBIA, 2019)
Abstract This study was conducted on Islamic Banking in Indonesia. The direction of this study to analyze financial performance of Islamic banking with income statement approach and value added approach. Population in this study is the 13 islamic Banks. The sample is taken using purposive sampling with specified criteria resulting 6 islamic Banking in Indonesia. This study conducted through Paired samples t-test by using SPSS 20. For testing the variable, researcher exercise financial rasio. The results show that : (1) There are significant differences on the ROA ratio if analyzed with income statement approach and value added approach, (2) There are significant differences toward ROE ratio with income statement approach dan value added approach, (3) There are significant differences on the LBAP ratio if analyzed with income statement approach and value added approach, (4) There are significant differences toward NPM ratio with income statement approach and value added approach. The overall results of the study are significant differences in financial performance with income statement approach and value added approach.